Long-term outcomes of drug-coated balloon treatment of calcified coronary artery lesions: a multicenter, retrospective, propensity matching study - Shan, Yingguang; Lu, Wenjie; Han, Zhanying; Pan, Sancong; Li, Xiangbing; Wang, Xi; Pan, Liang; Wang, Xule; Zheng, Xiaolin; Li, Ran; Zhou, Yanjun; Qin, Peng; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Coronary artery calcification (CAC) is associated with high rates of restenosis and adverse clinical events after percutaneous coronary intervention (PCI) with drug-eluting stents (DES). Objectives The aim of this study was to evaluate the long-term clinical outcomes of drug-coated balloon (DCB)-only treatment for de novo lesions with and without CAC. Methods Patients with de novo coronary disease treated with the DCB-only strategy were retrospectively enrolled from three centers and categorized into a CAC group and a non-CAC group. The primary endpoint was the target lesion failure (TLF) rate during the 3-year follow-up. Secondary endpoints included the occurrence of major adverse cardiac events (MACEs), target lesion revascularization (TLR), cardiac death, myocardial infarction (MI) and any revascularization. Propensity score matching (PSM) was conducted to assemble a cohort of patients with similar baseline characteristics. Results A total of 1,263 patients with 1,392 lesions were included, and 243 patients were included in each group after PSM. Compared with the non-CAC group, the incidence rates of TLF (9.52% vs. 4.94%, odds ratio [OR]: 2.080; 95% confidence interval [CI]: 1.083–3.998, P = 0.034) and TLR (7.41% vs. 2.88%, OR: 2.642; 95% CI: 1.206–5.787, P = 0.020) in the CAC group were higher. The incidence rates of MACE (12.35% vs. 7.82%, OR: 1.665; 95% CI: 0.951–2.916, P = 0.079), cardiac death (2.06% vs. 2.06%, OR: 0.995; 95% CI: 0.288–3.436, P = 0.993), MI (1.23% vs. 0.82%, OR: 2.505; 95% CI: 0.261–8.689, P = 0.652) and any revascularization (12.76% vs. 9.67%, OR: 1.256; 95% CI: 0.747–2.111, P = 0.738) were similar between groups. Conclusions CAC increased the incidence of TLF and TLR without a substantial increase in the risk of MACE, cardiac death, MI, or any revascularization in patients treated with DCB-only angioplasty during the 3-year follow-up.